And the Last Shall Be First: Heterochrony and Compensatory Marine Growth in Sea Trout (Salmo trutta) - Carlos Garcia De Leaniz (PLoS ONE, 2012)
Early juvenile growth is a good indicator of growth later in life in many species because larger than average juveniles tend to have a competitive advantage. However, for migratory species the relationship between juvenile and adult growth remains obscure. We used scale analysis to reconstruct growth trajectories of migratory sea trout (Salmo trutta) from six neighbouring populations, and compared the size individuals attained in freshwater (before migration) with their subsequent growth at sea (after migration). We also calculated the coefficient of variation (CV) to examine how much body size varied across populations and life stages. Specifically, we tested the hypothesis that the CV on body size would differ between freshwater and marine environment, perhaps reflecting different trade-offs during ontogeny. Neighbouring sea trout populations differed significantly in time spent at sea and in age-adjusted size of returning adults, but not on size of seaward migration, which was surprisingly uniform and may be indicative of strong selection pressures. The CV on body size decreased significantly over time and was highest during the first 8 months of life (when juvenile mortality is highest) and lowest during the marine phase. Size attained in freshwater was negatively related to growth during the first marine growing season, suggesting the existence of compensatory growth, whereby individuals that grow poorly in freshwater are able to catch up later at sea. Analysis of 61 datasets indicates that negative or no associations between pre- and post-migratory growth are common amongst migratory salmonids. We suggest that despite a widespread selective advantage of large body size in freshwater, freshwater growth is a poor predictor of final body size amongst migratory fish because selection may favour growth heterochrony during transitions to a novel environment, and marine compensatory growth may negate any initial size advantage acquired in freshwater.